PERANAN ARANSEMEN MUSIK GEREJA MODEREN TERHADAP DINAMIKA IBADAH - Eko AgusSetiawan (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2023)
Music arrangement is one of the important things to pay attention to its use in worship by everyone who is expected to make a positive contribution to the development of music specifically for the church, and in general for the Indonesian people in the future. This is one of the ways in which popular culture works in the modern church based on the author's understanding of the general values developed in worship by the church today as the foundation for the development of music at a later stage. This study uses a descriptive qualitative method with the process of collecting data through interviews, observation, and documentation of participants. Based on the data analysis conducted, it was concluded that the role of modern church music arrangements has an influence on the dynamics of church worship. In applying the role of church music arrangements to the dynamics of worship, music ministers need an understanding of the importance of musical arrangements and an understanding of how patterns of developing effective arrangements in carrying out worship activities.